Penerapan Metode Requirement Engineering dalam Pengembangan Website E-Commerce sebagai Media Promosi dan Pemasaran pada Kelompok UMKM Tenun Ikat - Meylano, Nunsio Handrian; Woda, Yanter Wilve Baly; Mukin, Dimas Pangestu; Pereira, Frederico Lino; Theresia, Destiana Evarista (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The utilization of digital marketing platforms, particularly E-Commerce, aims to support SMEs in engaging directly with consumers online, increasing sales conversion rates, reducing marketing costs, providing real-time customer service, and enhancing product competitiveness. E-Commerce enables businesses to reach broader markets without geographical limitations, whether locally, nationally, or internationally. Adopting this technology is a strategic step for business sustainability, as enterprises that do not leverage E-Commerce risk losing their competitive edge. Economic developments driven by technological innovation have significantly influenced business strategies, including those of the Tenun Ikat Mbola So SME group. Through the implementation of an E-Commerce application as a digital marketing platform, this SME can expand its market reach, reduce reliance on traditional marketing methods, and optimize marketing and promotional cost efficiency.